2022
DOI: 10.3390/cancers14133066
|View full text |Cite
|
Sign up to set email alerts
|

GNAQ and GNA11 Genes: A Comprehensive Review on Oncogenesis, Prognosis and Therapeutic Opportunities in Uveal Melanoma

Abstract: The GNAQ and GNA11 genes are mutated in almost 80–90% of uveal melanomas in a mutually exclusive pattern. These genes encode the alpha subunits of the heterotrimeric G proteins, Gq and G11; thus, mutations of these genes result in the activation of several important signaling pathways, including phospholipase C, and activation of the transcription factor YAP. It is well known that both of them act as driver genes in the oncogenic process and it has been assumed that they do not play a role in the prognosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 118 publications
0
31
0
3
Order By: Relevance
“…The genetic analysis of tumor samples in UM can help predict metastatic risk and manage patients. Monosomy 3 (M3) and BAP1 gene inactivation are strongly associated with poor prognosis ( 39 ), and patients with BAP1 inactivation are at high risk of metastasis ( 40 , 41 ). Among the four subtypes identified by Robert son AG et al., EIF1AX or SF3B1 alterations were associated with a lower risk of metastasis and a better prognosis ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic analysis of tumor samples in UM can help predict metastatic risk and manage patients. Monosomy 3 (M3) and BAP1 gene inactivation are strongly associated with poor prognosis ( 39 ), and patients with BAP1 inactivation are at high risk of metastasis ( 40 , 41 ). Among the four subtypes identified by Robert son AG et al., EIF1AX or SF3B1 alterations were associated with a lower risk of metastasis and a better prognosis ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the four subtypes identified by Robert son AG et al., EIF1AX or SF3B1 alterations were associated with a lower risk of metastasis and a better prognosis ( 41 ). Although there is no conclusive evidence that alterations in the GNAQ and GNA11 genes are relevant to UM prognosis and metastasis ( 39 ), a recent study reported a poorer prognosis for those with GNA11 mutations ( 42 ). In our results, the frequencies of GN A11 and BAP1 gene alterations were highest in the ICD high expression and high-risk groups, indicating a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…4. GNAQ/GNA11 subtype: GNAQ/GNA11 mutations are found in 80–90% of uveal melanomas [ 38 ]. These genes encode the alpha subunits of the heterotrimeric G proteins (Gq/G11) and their mutations activate various signaling pathways, acting as driver genes in the oncogenic process [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…GNAQ/GNA11 subtype: GNAQ/GNA11 mutations are found in 80–90% of uveal melanomas [ 38 ]. These genes encode the alpha subunits of the heterotrimeric G proteins (Gq/G11) and their mutations activate various signaling pathways, acting as driver genes in the oncogenic process [ 38 ]. Patients may be treated with MEK inhibitors since these genes’ activation leads to the activation of the MAPK pathway with MEK enzymes being one of its main effectors [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, GNAQ /11 mutations result in the constitutive activation of signaling cascades that promote cell proliferation and tumor progression in UM. The inhibition of these well-studied signaling pathways is a promising targeted therapeutic strategy , but requires prior knowledge of the patient’s mutational status.…”
Section: Introductionmentioning
confidence: 99%